The magnitude and impact of tobacco marketing exposure in adolescents' day-to-day lives: An ecological momentary assessment (EMA) study. (January 2019) - Roberts, Megan E.; Keller-Hamilton, Brittney; Hinton, Alice; Browning, Christopher R.; Slater, Michael D.; Xi, Wenna; Ferketich, Amy K.
Abstract: Purpose: Research indicates that tobacco marketing contributes to higher pro-tobacco attitudes and behaviors among adolescents, but no studies have been able to assess the impact of real-world tobacco marketing exposures in real-time. The purpose of this study was to examine the magnitude and impact of tobacco marketing exposure on adolescents using ecological momentary assessment (EMA). Our primary hypotheses were that (1) youth would most frequently report tobacco marketing at the retail points-of-sale and (2) greater exposures to tobacco marketing would be associated with more favorable tobacco-related attitudes, use, and expectancies. Methods: Participants were adolescent males from rural and urban Ohio ( N  = 176, ages 11–16). For ten days, these adolescents were prompted at two—three random times/day to complete a brief smartphone-based survey about their exposures and responses to tobacco-related advertising. Results: Adolescents reported exposures to tobacco marketing an average of 1.9 times over the 10-day EMA period, with over 10% seeing a tobacco advertisement 5 or more times. Reports of marketing exposures occurred most frequently at the point-of-sale; exposures were higher among tobacco users and rural adolescents. Consistent with hypotheses, marketing exposure was related to more positive attitudes to the tobacco advertisements, more tobacco use, and higher expectancies to use in the future. Conclusions: Overall, these findings signal the magnitude of tobacco marketing exposures and their pernicious impact on youth. Findings underscore the importance of federal, state, and local-level tobacco regulatory policies to protect youth from the marketing that puts them at risk for a lifetime of nicotine addiction and tobacco-related diseases. Highlights: Adolescents completed a 10-day ecological momentary assessment (EMA) study. EMA captured real-world tobacco marketing exposures in close to real-time. Point-of-sale marketing exposures occurred most frequently. Those reporting more exposures had more positive attitudes toward the ads they saw. Exposures were associated with higher tobacco use and expectancies for future use.